Building and interconnecting hydrogen networks: insights from the electricity and gas experience in Europe - Bento, N. (Energy Policy, 2008)
This paper aims to investigate the transition to a new energy system based on hydrogen in the European liberalized framework. After analyzing the literature on the hydrogen infrastructure needs in Europe, we estimate the size and scope of the transition challenge. We take the theoretical framework of network economics to analyze early hydrogen infrastructure needs. Therefore, several concepts are applied to hydrogen economics such as demand club effects, scale economies on large infrastructures, scope economies, and positive socio-economical externalities. Based on the examples of the electricity and natural gas industry formation in Europe, we argue for public intervention in order to create conditions to reach more rapidly the critical size of the network and to prompt network externalities, allowing for the market diffusion of and, thus, an effective transition to the new energy system.